(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
It is established that insulin induces overgrowth of rat thymic gland and elevation of free thymocytes in blood. It is assumed that insulin can antagonize 101 pro-apoptotic effect of glucocortycoids and this underlies mentioned events. In present study we examined the effect of insulin on the key apoptotic process in thymocytes – oligonucleosomal DNA fragmentation in nuclei. It was shown, that oligonucleosomal DNA fragmentation in isolated thymocyte nuclei could be performed without involvement of well-known inducers that are generated in apoptotic cytoplasm. According to our data in early stages of insulin treatment (1 and 4 h after administration), hormone suppresses the oligonucleosomal DNA fragmentation in rat thymocyte nuclei. Coming from these data a supposal was derived that anti-apoptotic effect of insulin could be mediated by hormone-induced suppression of the key nuclear apoptotic event in thymocytes – the oligonucleosomal DNA fragmentation.